Qatar’s Strategy for Promoting Creativity, Innovation, and the Development of Financial Technology - Debbache, Amira; Khemili, Farid (Journal of Research in Finance and Accounting, 2025)
This study aims to explore the State of Qatar's experience in fostering creativity, innovation, and the development of financial technology (FinTech) by examining the strategic framework established to support these objectives. Data and information were collected through various annual reports and official disclosures available on governmental websites. These sources were then organized, analyzed, and interpreted. The study concludes that Qatar places significant emphasis on promoting creativity and innovation, particularly in priority sectors. A long-term strategy has been developed to enhance the country’s position in various forms of innovation and creative advancement.